Acute Transverse Myelitis (Ascending Myelitis) as the Initial Manifestation of Japanese Encephalitis: A Rare Presentation - Varshney Ankur Nandan; Kumar Nilesh; Behera Dibyaranjan; Tiwari Ashutosh; Anand Ravi; Anand Arvind (Case Reports in Infectious Diseases)
Japanese encephalitis, an inflammatory brain disease prevalent in Southeast Asia, usually presented with fever, headache, convulsions, brain stem signs with pyramidal and extrapyramidal features, and altered sensorium. Acute transverse myelitis, as the initial manifestation of Japanese encephalitis, is an unusual manifestation and is seldom reported. We hereby report a case of 13-year-old adolescent boy who presented to us with fever and acute onset paraparesis with urinary retention initially, progressing to quadriparesis and then followed by headache and altered sensorium. Brain MRI revealed bilateral basal ganglia that were grossly swollen with vasogenic edema tracking along internal capsule and midbrain. Adjacent ventrolateral thalamus and internal capsule also showed mild abnormal intensities. Spinal screening showed abnormal cord intensities in entire cord with gross edema in cervical and conus regions. He had elevated IgM titres against JE virus in cerebrospinal fluid. The patient was treated conservatively along with intravenous methyl prednisolone for 5 days. He regained near normal power at 3 months in followup, but hesitancy, dysarthria, and slowness of movement still persisted. To conclude, a young boy presenting with ATM in an endemic region of JE, then a possibility of Japanese encephalitis, should be sought by clinicians as early use of immunomodulator shows survival benefit.